Analysis of Broiler Feed Distribution Channel (Case Study at PT. Sinar Terang Madani Makassar) - Aswad Aswad; Aslina Asnawi; Hastang Hastang (Hasanuddin Journal of Animal Science (HAJAS), 2022)
ABSTRACT In the context of supporting the establishment of a profitable livestock business, a livestock feed industry that can supply livestock feed at a feasible price needs to be developed. Feed mill is constantly developing into large scale at the same time the increased population of broiler. The current research was carried out to determine distribution pattern, marketing margin, marketing profit, thus the efficiency of broiler feed marketing at PT. Sinar Terang Madani can be determined. This research was conducted in August-September 2021 at PT. Sinar Terang Madani through descriptive research that employed both quantitative and qualitative data. Furthermore, the data sources employed were primary data and secondary data. In this case, the data were collected through observation, interviews, and snowball sampling. Based on the research that has been conducted, it indicates that there are three forms of feed marketing distribution channels. In this case, the first distribution channel is the direct marketing from PT. Sinar Terang Madani to consumers. The second distribution channel is from PT. Sinar Terang Madani which is sold through retailers and then consumers. Meanwhile, the third distribution channel is from PT. Sinar Terang Madani which is marketed through agents and then to retailers and eventually to consumers. From those three distribution channel, the one that has the highest margin is the third distribution channel with a total margin of IDR 53,750/sack, while the lowest is the second distribution channel of IDR 35,000/sack. Furthermore, the distribution channel that has the largest marketing cost is the third distribution channel with an average total cost of IDR 3,816/sack, while the smallest is the second distribution channel with an average total cost of IDR 1,240/sack. In addition, the distribution channel that has the largest marketing profit is the third distribution channel with a total profit of IDR 46,118/sack, while the smallest is the second distribution channel of IDR33,760/sack. Based on the results obtained, it was concluded that the marketing that was done through the three forms of broiler feed distribution channels at PT. Sinar Terang Madani is considered efficient because it obtains an efficiency value between 0.2%-0.9%. Keywords: Distribution Channel, Margin, Cost, Profit, and Marketing Efficiency.